(untitled) (Medical Forum Monthly, 2024)
Objective: To evaluate the presence and spread of environmental pathogens and their sensitability at burns ward civil hospital Karachi. Study Design: Descriptive observational study. Place and Duration of Study: This study was conducted at Burns Center, Civil Hospital, Karachi during 2012. Materials and Methods: Samples were collected of air and examined through air microbe index. Samples of water were collected from different sources. Similarly samples were also collected from clothes, nails, hairs and hands of all the Health care personnel working in the burns ward. These samples were sent for culturing to conclude for presence of bacteria. Results: Staphylococcus Aureus was the major organism obtained from the samples in the burns ward. The organism was also detected from the nasal swabs taken from some staff members. Being the most common cause of nosocomial infection it is necessary to take appropriate steps to cut the probable route of transmission. E.coli and Pseudomonas strains were also detected from the environment of the burns ward. E.coli was also detected in the food trays of the patient a probable route of transmission. Many of these strains were resistant to antibiotics which made it further difficult to treat them. Strains of Enterobacteriaceae, Proteus Mirabilis, Klebsiella and Citrobacter were collected from our personnel and were responsible for some hospital acquired infections. Conclusion: Staphylococcus Aureus was the major organism found. The major routes of transmission of opportunistic organisms were tap water and our staff members. Proper hygiene measures and awareness programs for the staff members should be carried out to aware them of the importance of hygiene.